Methods of estimation of bodily condition of sportsmen of different qualification, specialized in at run on short and middle distances - Kryvoruchenko O.V (Kharkov National Pedagogical University, 2012)
The method of estimation of bodily condition of sportsmen of different qualification, which are specialized in at run on short and middle distances, is presented. A method takes into account the informing criteria of estimation of physical preparedness and functional state of the cardiovascular system of sportsmen. It contains the complex of pedagogical tests, evaluation tables, model indexes of cardiography, determinations of type of the vegetative adjusting of cardiac rhythm and classification of the functional states of sportsmen. 110 skilled sportsmen took part in an experiment (men, age is 16 - 21 year). Indexes, which possibility operatively to estimate the bodily condition of sportsmen, select leaders from the group of sportsmen with an identical sporting result for the subsequent including in the complement of collapsible command is on, are set. Directions of prognostication of sporting result of concrete sportsman are rotined.